Evaluasi Peran Economic Value Added (EVA) Sebagai Penilaian Kinerja Manajemen Perusahaan dalam Era Bisnis Kontemporer - Rizal R. Manullang; Ruki Ambar Arum; Sunarni; Rani Suryani; Yanti Budiasih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to initiate the role of Economic Value Added (EVA) as an assessment of corporate management performance in the contemporary business era. The approach method used in this study is a literature study to assess the effectiveness of Economic Value Added (EVA). In addition, this study also provides practical suggestions for the application of Economic Value Added (EVA) and aims to deepen the understanding of corporate management performance assessment. The findings in this study indicate that Economic Value Added (EVA) offers a comprehensive approach by considering cost capital, providing a more accurate picture of the increase in company value. However, the use of Economic Value Added (EVA) also requires strong analytical skills and access to complete data, and must be combined with other evaluation methods to provide a holistic understanding of company performance.